Skill development in backstroke kicking: Implications for instructors - Myres, K.; Sanders, R. (coachesinfo.com)
This study of backstroke kicking is the second in a series investigating the development of proper technique in swimming and the implications for improving teaching effectiveness. Swimming Nature Ltd (SNL) advocates teaching backstroke (see What Stroke Should Be Taught First?) as a first stroke because it is a more natural way of swimming. It is less difficult then freestyle because the swimmer`s face is not in the water to complicate breathing. Additionally, backstroke skills can then be easily transferred to learning freestyle skills and thus promoting faster and more efficient learning.